Investigating the Prevalence of Ectasia in Angiographic Patients with Acute Coronary Syndrome : Ectasia in Angiographic Patients with ACS - Farooq, Anam; Tariq, Ayesha; Aslam, Muhammad Arslan; Sharif, Asma; Ahmed, Waseem; Haider, Ali Saqlain (Pakistan Journal of Health Sciences, 2024)
Coronary artery ectasia is dilatation of a segment of the coronary arteries leading to intense cardiac conditions. Among the patients undergoing angiography, it has a rare prevalence of 0.3 – 5.3%. It has been strongly associated with atherosclerosis as an evident cause of the dilation of coronary lumen. Objective: To determine the frequency of ectasia in patients of acute coronary syndrome undergoing coronary angiography. Methods: It is a cross sectional study conducted over six months. 160 patients from the Department of Cardiology, Mayo Hospital, Lahore were enrolled that fulfilled the study criteria of 30-70 years of age, presenting acute coronary syndrome, and undergoing angiography. The Angiography was done by an expert surgeon, simultaneously observed by one of the researchers. Ectasia was diagnosed in all the 160 based on its operational definition. Socio-demographic information including name, age, sex, diabetes (BSR>200mg/dl), hypertension (BP≥140/90mmHg), smoking, and type of acute coronary syndrome was collected with informed consent. Statistical analysis was performed using SPSS version 21. The chi-square test was practiced comparing ectasia in stratified groups of socio-demographic characters and type of acute coronary syndrome. Results: Ectasia was diagnosed in 54 (33.8%) patients. No significant association was seen between the age of patients and ectasia. However, frequency of ectasia was higher in patients in the age group 30-50 years. Frequency of ectasia was higher among male patients, but it was not statistically significant when compared with frequency of ectasia among female patients. No significant association was seen between ectasia and diabetes (p-value > 0.999), hypertension (p-value = 0.439) and smoking status (p-value = 0.140) of patients. Conclusions: Ectasia is a well-established condition of coronary artery but is an unconventional diagnostic finding of coronary angiography in patients affected with acute coronary syndromes.